Cross-cultural adaptation for Colombia and content validity of the RAC scale for assessing the risk of infection in hospitalized adults - Rodríguez-Acelas, Alba Luz; López de Ávila, Mónica; Yampuezán Getial, Daniela; de Abreu Almeida, Miriam; Cañon-Montañez, Wilson (Revista Cuidarte, 2021)
Introduction: Health care–associated infections (HAI) are a serious public health problem, which can be prevented by identifying risk factors with the use of scales. Objective: To adapt cross-culturally and perform content and face validation of the Rodríguez-Almeida-Cañon (RAC) scale for assessing the risk of infection in hospitalized adults. Materials and Methods: Methodological study of cross-cultural adaptation. Data collection was carried out from June to November 2020. The sample consisted of 11 specialists. The RAC scale was evaluated as a whole, determining its scope, the items were evaluated individually, verifying their clarity, relevance and pertinence. To evaluate each item, a four-level Likert-type scale was used. The content validity was evaluated through the content validity index (CVI). Results: Through the evaluation of the committee of specialists it was possible to determine that the RAC scale is suitable for use in the Colombian cultural context. Adjustments were made to improve the interpretation of some items. The CVI of the items was between 0.90 to 1.0 and the average CVI of the scale was 0.98. Discussion: This scale makes it possible to measure the HAI risk at a low cost, in order to be able to plan and execute interventions by the multidisciplinary team in charge of the health and care of the patient. Conclusions: The RAC scale in its Spanish version is an appropriate instrument for assessing the risk of HAI in hospitalized adults in Colombia.How to cite this article: Rodríguez-Acelas Alba Luz, López de Ávila Mónica, Yampuezán Getial Daniela, De Abreu Almeida Miriam, Cañon-Montañez Wilson. Adaptación transcultural para Colombia y validez de contenido de la escala RAC de evaluación del riesgo de infección en el adulto hospitalizado. Revista Cuidarte. 2022;13(1): e2406. http://dx.doi.org/10.15649/cuidarte.2406
Keywords: Risk Assessment; Infection Control; Cross-Cultural Comparison; Validation Study; Patient Safety